Plant-based shape memory cryogel for hemorrhage control - Deng, Jingyu (2024)
The escalating global demand for sustainable manufacturing, motivated by concerns over energy conservation and carbon footprints, encounters challenges due to insufficient renewable materials and arduous fabrication procedures to fulfill specific requirements in medical and healthcare systems. Here, biosafe pollen cryogel is engineered as effective hemostats without additional harmful crosslinkers to treat deep noncompressible wounds. A straightforward and low-energy approach is involved in forming stable macroporous cryogel, benefiting from the unique micro-hierarchical structures and chemical components of non-allergenic plant pollen. It is demonstrated that the pollen cryogel exhibits rapid water/blood-triggered shape-memory properties within 2 s. Owing to their inherent nano/micro hierarchical structure and abundant chemical functional groups on the pollen surface, the pollen cryogel shows effective hemostatic performance in a mouse liver penetration model, which is easily removed after usage. Overall, the self-crosslinking pollen cryogel in this work pioneers a framework of potential clinical applications for the first-hand treatment on deep noncompressible wounds.